Preparation of Ziegler-Natta/Ionic Liquild Modified Clay Compound Catalyst and its Catalysis During Preparation of Poly(propylene)/Clay Nanocomposites - Wang, L.M. (Asian Journal of Chemistry, 2011)
Ziegler-Natta/ionic liquid modified clay compound catalyst was prepared with dibutylphthalate as internal donor. Poly(propylene)/clay nanocomposites were synthesized with this compound catalyst in combination with triethyl aluminium as cocatalyst and dipenyldimethoxylsilane as an external donor by in situ intercalative polymerization. The stereospecificity of compound catalyst didn't fall down sharply because of the existence of clay and bisalkylimidazolium. Catalytic efficiency of compound catalyst could rise by pretreatment of compound catalyst. Poly(propylene) obtained in composites was high isotacticity poly(propylene). Both wide angle X-ray diffraction (XRD) analysis and transmission electron microscopy (TEM) images showed clay layers were exfoliated into nanometer size in poly(propylene) matrix.